2019
DOI: 10.1002/chem.201902724
|View full text |Cite
|
Sign up to set email alerts
|

15N Hyperpolarization of Dalfampridine at Natural Abundance for Magnetic Resonance Imaging

Abstract: Signal Amplificationb yR eversible Exchange (SABRE)i sapromising methodf or NMR signal enhancement and production of hyperpolarizedm olecules. As nuclear spin relaxation times of heteronuclei are usually much longer than those of protons, SABRE-based hyperpolarization of heteronuclei in molecules is highly important in the context of biomedical applications.I nt his work, we demonstrate that the SLIC-SABRE technique can be successfully used to hyperpolarize 15 Nn uclei in dalfampridine.T he high polarization l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 40 publications
1
34
1
Order By: Relevance
“…To overcome these short T 1 s, other nuclei such as 15 N, could be utilized, especially when combined with a heterogeneous approach . Recent studies have shown that 15 N‐based polarization can be detected at high‐field via spin lock induced crossing (SLIC)‐SABRE, which has been exemplified for pyridine and nicotinamide, as well as dalfampridine, a drug which is used in the treatment of multiple sclerosis . The pyridyl nitrogen of dalfampridine was enhanced by over 32,000‐fold.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these short T 1 s, other nuclei such as 15 N, could be utilized, especially when combined with a heterogeneous approach . Recent studies have shown that 15 N‐based polarization can be detected at high‐field via spin lock induced crossing (SLIC)‐SABRE, which has been exemplified for pyridine and nicotinamide, as well as dalfampridine, a drug which is used in the treatment of multiple sclerosis . The pyridyl nitrogen of dalfampridine was enhanced by over 32,000‐fold.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, a number of radiofrequency (RF) pulse sequences have been developed over the years which allow polarization transfer to heteronuclei such as LIGHT‐SABRE, [43] ADAPT‐SABRE, [44] SLIC‐SABRE, [45,46] INEPT‐SABRE, [47,48] QUASR‐SABRE, [49] and DARTH‐SABRE [50] . While the efficiency of these RF‐based approaches was inferior to SABRE‐SHEATH when pyridine was employed as a substrate, recently some of us have demonstrated that P 15N of ∼7–8 % can be achieved for 4‐dimethylaminopyridine and 4‐aminopyridine (dalfampridine, FAM) using SLIC‐SABRE [51] . Such high 15 N polarization levels allowed to demonstrate the feasibility of 15 N magnetic resonance imaging (MRI) at the natural abundance of 15 N nuclei [51] .…”
Section: Introductionmentioning
confidence: 99%
“…Some notable work has been done on polarization transfer to 15 N nuclei to extend hyperpolarization lifetimes to many minutes [42–44] . For instance, SABRE of nitrogen‐containing drugs is exemplified by HP fampridine which made it possible to perform 15 N MRI at natural abundance of the 15 N isotope [45] …”
Section: Figurementioning
confidence: 99%
“…[42][43][44] For instance, SABRE of nitrogen-containing drugs is exemplified by HP fampridine which made it possible to perform 15 N MRI at natural abundance of the 15 N isotope. [45] The joint CRDF project mentioned earlier, in addition to its successfully achieved primary objective of demonstrating HET-PHIP effects, encompassed numerous other objectives which were rather challenging and ambitious. One of those was about the use of ultralow field NMR to monitor catalytic processes in metal containers.…”
mentioning
confidence: 99%